Mapping Urban Proximity for Resilience: Testing a Methodological Framework for Local Resilience Units in Turin - Brunetta, Grazia; Scalas, Mattia; Voghera, Angioletta (Contesti. Città, territori, progetti, 2026)
Growing awareness of the climate change effects made sustainability and resilience essential in the debate on territorial planning, yet their practical deployment is still constrained by siloed programmes and sector‑based strategies. The Post Un‑Lock project addresses this gap by introducing the Local Resilience Unit (LRU), an operational framework that translates urban‑resilience theory into place‑specific action. Each LRU blends territorial analysis with community co‑design to reinforce a city’s and neighbourhood capacity to absorb shocks while preserving wellbeing and quality of life. This article describes an open‑source GIS workflow - implemented in QGIS and OpenRouteService - for the identification of potential LRUs. After compiling a neighbourhood‑scale inventory of everyday points of interest, isochrone‑based service areas are generated for each facility under the paradigm of a walkable, proximity‑oriented city. Overlaying these service areas delineates zones of high pedestrian accessibility, which are considered the most suitable locations for resilience‑oriented interventions. The methodology is demonstrated in Turin, Italy. The results of the study provide a foundation for future deployment of LRUs both within Turin and in other urban contexts, and can be extended wherever identifying areas for essential services is required.